Junior High School Student’s Knowledge About Local Potential of Lake Rawa Pening in Relation to Science Learning - Keliat, Natalia Rosa; Nuryani, Ika Maulida; Hastuti, Susanti Pudji (Universitas Negeri Jakarta, 2025)
Lake Rawa Pening is one of the natural resources with abundant local potential that can be utilized in the world of education and the surrounding community. The objectives of this study are: a) to determine the local potential of Lake Rawa Pening, and b) to determine the level of knowledge of junior high school students about Lake Rawa Pening related to local potential of the Lake in relation to science learning materials. The subjects of the study were grade IX junior high school students in eight schools around Lake Rawa Pening. Interviews and tests were used fordata collection technique. Data analysis were carried out by calculating students' scores and interpreting them into the minimum completion criteria (KKM) category by the Ministry of Education and Culture. Based on the results of the study, it is known that there are twenty-four types of fish, one type of lobster, one type of shellfish, five types of birds, twenty types of plants, and two types of inanimate objects that are included in the local potential of Lake Rawa Pening. Based on the results of the study, the average value of junior high school students' knowledge about the local potential of Lake Rawa Pening in relation to science learning materials only reaches 63, which it is categorized as insufficient. It was found that students' knowledge in insufficient category is 77%, the sufficient category is 19%, the good category is 4%, and no students were found to have knowledge in the very good category.